2021
DOI: 10.25273/etj.v9i1.8890
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanics Accuracy of Students’ Writing

Abstract: <span>In writing courses, the students tend to be more aware of technical errors in writing including the mechanics. Conversely, they tend to focus more on the idea or content of their writing when they produce papers to fulfill the assignment of non-writing courses. Whereas, the punctuation errors and misspelled words will make the meaning of the sentence ambiguous. This study aims to find out the degree of mechanics accuracy of students’ writings and what kind of mechanics mistakes mostly produced. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 4 publications
1
9
1
Order By: Relevance
“…Their instructors also agreed with these beliefs. Nazim and Mohammad (2022), Sandrawati andJurianto (2021), andYuliawati (2021) also discovered that the highest number of punctuation mistakes made by EFL learners were related to the use of commas and the absence of periods in their writings.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Their instructors also agreed with these beliefs. Nazim and Mohammad (2022), Sandrawati andJurianto (2021), andYuliawati (2021) also discovered that the highest number of punctuation mistakes made by EFL learners were related to the use of commas and the absence of periods in their writings.…”
Section: Discussionmentioning
confidence: 93%
“…Ahmed (2021) noticed 33% of mechanical errors in the pilot test of the study. Yuliawati (2021) and Darmawan (2023) exclusively studied mechanical errors in detail in their studies. Yuliawati (2021) reported that after analyzing 65 writing assignments from three nonwriting courses, participants' mistakes were the most in punctuation and the least in numbering.…”
Section: Previous Studies On Errors In Mechanics In L2 Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea should be structured and connected which can make writing understandable, thus students should have many vocabularies and understand the structure of the sentences (Sholikhatun, 2022). The structure of idea related to the mechanics of writing such as capitalization, punctuation and spelling (Yuliawati, 2021;Maharani & Sholikhatun, 2022). These elements of mechanics can influence the producing text of writing, in case of how people use it correctly.…”
Section: Introductionmentioning
confidence: 99%
“…In order to produce a good writing, students should pay a certain amount of commitment, practice, and hardwork (Yuliawati, 2021) because there are some components in writing that must be concerned such as grammar, vocabulary, and mechanics. Grammar is a theory of language of how language is put together and how it works (Gerot & Peter, 1995).…”
Section: Introductionmentioning
confidence: 99%